Growth of the cranial base and its influence on the position of the maxilla and mandible – a literature review - Perkowski, Konrad; Szpinda-Barczyńska, Anna; Kamiński, Konrad (Forum Ortodontyczne / Orthodontic Forum, 2020)
Cranial base synchondroses are endowed with a specific growth potential, and they contribute to the expansion of ossification centers and permit the cranial base to continue growing until it reaches its ultimate dimensions. The sphenooccipital synchondrosis allows for elongation of the basicranial axis, thus providing an appropriate space for the development of the maxillary alveolar process and teeth. Aim. The purpose of this article was to present growth of the cranial base in the prenatal and postnatal period, including the timing of closure of cranial base synchondroses and their significance in comprehensive cranial growth, along with some changes in the position of the maxilla and mandible, which are crucial for the final outcome of orthodontic treatment. Material and methods. Based on databases (Scopus, ScienceDirect, BIOSIS, EMBASE and PubMed), 27 original papers published between the years 1958–2017 were ultimately analyzed in the aspect of prenatal cranial growth, the timing of closure of cranial base synchondroses and their roles in combined cranial growth. The following search criteria were used: cranial growth, chondrocranium, sphenooccipital synchondrosis and malocclusions. Conclusions. Cranial synchondroses enable the cranium to grow in a combined and integrated fashion. The results of studies on cranial base development allow to predict growth changes of the maxilla and mandible. During orthodontic treatment of patients in the developmental age, growth prediction must be taken into account. Orthodontic treatment of a growing patient must include not only thoroughly planned biomechanics but also growth changes that can promote or impede achievement of treatment objectives. (Perkowski K, Szpinda-Barczyńska A, Kamiński K. Growth of the cranial base and its influence on the position of the maxilla and mandible – a literature review. Orthod Forum 2020; 16 (1): 37-44).